Pregnancy in Polycystic Ovary Syndrome I: Lessons from a Pragmatic Explanatory with Repository Clinical Trial - Legro, Richard S. (Seminars in Reproductive Medicine, 2015)
This article reports results from a multicenter pragmatic study, with explanatory components and also with a repository, the Pregnancy in Polycystic Ovary Syndrome I study (Clinicaltrials.gov: NCT00068861), which we label with the acronym PERCT. This was a study conceived and conducted by the Steering Committee of the Reproductive Medicine Network. We discuss the publication structure from the study, including concept, protocol baseline, primary and secondary outcome papers, as well as ancillary papers related to studies conducted using biosamples from the study repository. We demonstrate that the primary outcome paper remains far and away the most impactful publication from this study. However, we note also that other related publications, including the baseline paper and some papers related to secondary hypotheses, such as prediction models, can still be relatively impactful. However, the most impactful ancillary publications arose from utilizing specimens in the repository to test post hoc hypotheses. Therefore, establishing a repository of serum and DNA samples, and potentially other biological specimens (i.e., semen, urine, biome samples, etc.) and making these specimens and data available to investigators may provide further meaningful productivity to a large pragmatic multicenter trial known here as PERCT.
Keywords: infertility; hyperandrogenism; randomized clinical trial; insulin resistance